2006
DOI: 10.1614/ws-06-009.1
|View full text |Cite
|
Sign up to set email alerts
|

Tillage systems and seed dormancy effects on common waterhemp (Amaranthus tuberculatus) seedling emergence

Abstract: Understanding weed seedling emergence patterns is important for successful implementation of many weed management strategies. Identifying the sources of variation of emergence patterns could greatly improve our ability to predict emergence timing. Differences in seed dormancy levels between populations or biotypes are usually not considered when studying seedling emergence of many weed species despite evidence that dormancy levels can affect weed seedling emergence patterns. We studied the importance of seed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…The varying response to temperature in biotypes exists in other weed species including waterhemp [Amaranthus tuberculatus (Moq.) Sauer] (Leon and Owen 2006) and redroot pigweed (Weaver and Thomas 1986).…”
Section: Soil Temperaturementioning
confidence: 99%
“…The varying response to temperature in biotypes exists in other weed species including waterhemp [Amaranthus tuberculatus (Moq.) Sauer] (Leon and Owen 2006) and redroot pigweed (Weaver and Thomas 1986).…”
Section: Soil Temperaturementioning
confidence: 99%
“…For example, previous studies demonstrated that populations of tall waterhemp [Amaranthus tuberculatus (Moq.) Sauer], a dioecious weed species, have evolved different mechanisms to control seed dormancy and germination (Leon et al 2006a(Leon et al , 2006b, and these differences affected seedling emergence patterns depending on tillage system (Leon and Owen 2006). Furthermore, Bond and Oliver (2006) found differences in leaf traits among Palmer amaranth accessions collected throughout the southern United States and proposed that these might be ecotypes, but their research did not address the causes of those differences.…”
mentioning
confidence: 99%
“…Thus, soil disturbance is minimized and crop residues remain on the top soil (Putte et al, 2010). Hence, it is not just an elimination of ploughing; it involves the development of a combination of agroecologically sound management practices (Han et al, 2013), changes in soil processes, lower soil temperature, and high soil moisture (Addae et al, 1991;Blevins and Frye, 1993;Leon and Owen, 2006), which could influence the ecosystem services, and the biodiversity too (Palm et al, 2014). Although, the environmental consequences of adopting CT (Holland, 2004) have been widely discussed, the slow pace of growth due to weed menace is a cause of concern.…”
Section: Introductionmentioning
confidence: 99%